Lord Salisbury ve Osmanlı İmparatorluğu'na dair siyaseti (1876-1902) - Atalay, Onur (My University, 2024)
Lord Salisbury, tam ismiyle Robert Arthur Talbot Gascoyne-Cecil, 3 Şubat 1830’da İngiltere’de oldukça köklü aristokrat bir ailenin üyesi olarak doğdu. 1853 yılında Stamford’u temsilen Muhafazakâr Parti’den parlamento üyesi olarak, Avam Kamarası’na girdi. Siyasi kariyerinin ilerleyen dönemlerinde 1866-67 ve 1874-1878 yıllarında olmak üzere iki defa Hindistan Bakanlığı yaptı. Bunun yanında, 23 Aralık 1876-20 Ocak 1877 tarihleri arasında İstanbul (Tersane) Konferansı’nda fevkalade temsilci sıfatıyla ülkesini temsil etti. 1878-80 yılları arasında ilk defa Dışişleri Bakanlığı yaptı. Bu dönemde ülkesini temsilen Berlin Kongresi’ne katıldı. Sonrasında Benjamin Disraeli’nin 1881’deki vefatıyla, partisinin Lordlar Kamarası’ndaki lideri oldu. 1885-86, 1886-92 ve 1895-1902 yılları arasında üç defa başbakanlık yaptı. Başbakanlıkları sırasında 1885-86, 1887-92 ve 1895-1900 yılları arasında olduğu gibi genellikle Dışişleri Bakanlığı görevini de kendisi üstlendi. 1902 yılında emekli oldu ve 1903’te vefat etti. Lord Balfour, Lord Curzon ve Lord Robert Cecil gibi İngiliz diplomasisinin önemli isimlerinin gelişimine katkıda bulundu. Lord Salisbury öncesinde İngiliz hariciyesinin Osmanlı siyaseti özellikle 18. Yüzyıldan itibaren şartlara bağlı olarak dönemden döneme büyük değişkenlik gösterdi. Lord Salisbury’nin Osmanlı İmparatorluğu’na dair siyaseti ise, kendisinin realist dış politika anlayışı çerçevesinde şekillendi. Bu sebeple Lord Salisbury, İngiliz menfaatlerine göre belirli dönemlerde Osmanlı İmparatorluğu’nu destekledi, belirli dönemlerde ise Osmanlı İmparatorluğu’nun menfaatlerine zıt bir siyaset takip etti.

Lord Salisbury, with his full name Robert Arthur Talbot Gascoyne-Cecil was born on 3rd February 1830 as a member of a well-established aristocratic family. In 1853 he entered into House of Commons for Conservative Party as a member of parliament for Stamford. In the advancing periods of his political career, he became Secretary of State for India for two times in the years between 1866-1867 and 1874-1878. Besides that he represented his country as an extraordinary delegate in Istanbul (Shipyard) Conference which was held between 23rd December 1876 and 20th January 1877. He became Secretary of State for Foreign Affairs for first time in the years between 1878-1880. In this period he joined Berlin Congress as a delegate of his country, Thereafter, he became his party’s leader in the House of Lords when Benjamin Disraeli died in 1881. He became prime minister for three times in the years between 1885-86, 1886-92 and 1895-1902. During he held prime minister’s office, generally assumed the position of Secretary of State for Foreign Affairs as well. He retired in 1902 and died in 1903. He contributed development of some important people for British diplomacy such as Lord Balfour, Lord Curzon and Lord Robert Cecil. Before the period of Lord Salisbury, British foreign policy on Ottoman Empire has varied from period to period according to conditions espacially since 18th century. And Lord Salisbury’s policy on Ottoman Empire took shape within his realistic understanding of foreign policy. Threrefore he supported Ottoman Empire in some periods and he carried out a policy against the interests of Ottoman Empire in some periods according to British interests.
Keywords: Başbakan; British diplomacy; Dış ilişkiler; Dışişleri Bakanı Lord Salisbury; Foreign relations; Great Britain; İngiliz diplomasisi; İngiltere; Lord Salisbury; Osmanlı İmparatorluğu; Ottoman Empire; Prime Minister; Secretary State for Foreign Affairs; Sultan Abdulhamid II; Sultan II. Abdülhamid